Inducible Synthesis of Bacterial Luciferase: Specificity and Kinetics of Induction - Coffey, John J. (1967)
A nitrate-utilizing strain of marine bacteria was isolated in which luciferase was inducible by l-arginine. The induction was highly specific; structural analogues of arginine were ineffective, as were other natural amino acids. Several metabolites of arginine acted as weak inducers but did not affect the rate of induction in limiting concentrations of arginine. Hence, these compounds probably exerted a sparing effect on intracellular arginine. The kinetics of induction were followed by measurement of light output from intact cells, under conditions in which in vivo light output was determined only by the luciferase level. No enzyme appeared in the cells for 12 min after the addition of inducer, although the primary structure of the luciferase molecule was apparently synthesized within 2 to 4 min. It is proposed that during the remaining 8 to 10 min a precursor of luciferase was converted to active enzyme. The differential rate of synthesis rose during the first 5 min of induction, apparently as messenger ribonucleic acid accumulates in the cells; thereafter it remained constant for approximately 100 min.